2015
DOI: 10.1163/2667078x-01602002
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequality and the Rise of Localism in Hong Kong

Abstract: An increasing number of people define themselves as Hong Kong citizens or as Chinese Hong Kong citizens, rather than as Chinese citizens. This shift in identity accompanies growing social inequality, revealed by Hong Kong’s Gini Coefficient increasing from 0.525 in 2001 to 0.537 in 2011. Rising social inequality has led to localism/local-based nationalism. Is there a relationship between social inequality and increased localism? This paper argues that the growth of social inequality and increased localism in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…For example, Siu (2009) demonstrates that Hong Kongers perceive mainland Chinese as rural and poor (p. 118) and attribute the conditions of new immigrants ( xin yiming ) to ‘differences in cultural orientation, social status, and economic well-being from people like themselves (p. 119)’. Some Hong Kongers believe these new immigrants (especially those with fewer skills) rely heavily on social assistance and compete for a limited supply of public housing, schools, and hospital resources (Lee et al, 2016; Nagy, 2015). Wang (2012) found that Hong Kongers devalue Mainlanders regardless of the level of skills they possess.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Siu (2009) demonstrates that Hong Kongers perceive mainland Chinese as rural and poor (p. 118) and attribute the conditions of new immigrants ( xin yiming ) to ‘differences in cultural orientation, social status, and economic well-being from people like themselves (p. 119)’. Some Hong Kongers believe these new immigrants (especially those with fewer skills) rely heavily on social assistance and compete for a limited supply of public housing, schools, and hospital resources (Lee et al, 2016; Nagy, 2015). Wang (2012) found that Hong Kongers devalue Mainlanders regardless of the level of skills they possess.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Racial/ethnic preference or discrimination, however, does not solely occur between Caucasians and locals in Hong Kong. With the increasing number of mainland Chinese immigrants and Hong Kong localism, numerous studies have found that mainland Chinese face hostility from locals, thus hindering their integration into the local society (Law and Lee, 2007; Lowe and Tsang, 2017; Nagy, 2015; Ng et al, 2015; Tian, 2019). To address these issues of discrimination, the Hong Kong government made discrimination against new Chinese immigrants illegal and extended the Race Discrimination Ordinance to include people from China (Bauhinia Foundation Research Centre, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater differences among groups in 2009 may reflect the rise of anti-China sentiments following the 2008 Beijing Olympics, when the strength of national identity of Hong Kongers reached a peak (Ma, 2015). These sentiments are reportedly caused by factors such as perceived increase of Beijing's intervention in Hong Kong internal affairs (Ma, 2015;So, 2016), the protracted democratization process (Ortmann, 2015) and the negative effects of rapid Hong Kong-Mainland socio-economic integration (Lui, 2015;Nagy, 2015). These contexts continued to be exacerbated after 2009, leading eventually to the emergence of "localism" in the early 2010s.…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent, there has been an escalating social unrest in Hong Kong over the past twenty years (i.e., the 2003 1 st of July protest and the 2014 Umbrella Revaluation). It is generally believed that beneath the political issues about democratic rights which trigged the protests directly, there is also a bedrock of economic and social conditions that nurtured the development of social unrest, in which the city-state's rising inequality and extreme concentration of wealth is the most important one (Ng, 2013;Nagy, 2015;So, 2016;Dieter, 2019).…”
Section: Introductionmentioning
confidence: 99%